A study of the indian taxation system on cryptocurrency - Arora, Jyoti; Kaur, Lakhwinder (Gyan Management Journal, 2023)
Cryptocurrencies are digital tokens that allow people to make payments directly to each other through an online system. Since it can be used to buy and sell items and has the ability to store value and increase in value, cryptocurrency is drawing the attention of a lot of investors. As to the nature of cryptocurrency, there are different sets of opinions as to whether it is a currency or a Commodity or Security. The Finance Act 2022 was the first law to recognize Virtual Digital Assets (VDAs) in India and introduced crypto taxes. Accordingly, the income generated from investment in cryptocurrency is subject to tax. The present paper studies the emerging cryptocurrency market in India and the provisions of prevailing income tax law in India related to the taxation of cryptocurrency.